Transcanal Endoscopic Management of Middle Ear Paragangliomas - Surmelioglu, Ozgur; Bajin, Munir Demir; Kaya, Isa; Okuyucu, Semsettin; Ozturk, Kayhan; Orhan, Kadir Serkan; Celik, Mehmet (Lippincott Williams & Wilkins, 2023)
ObjectiveTo evaluate the clinical and audiological outcomes of transcanal endoscopic resection of middle ear paragangliomas.Study DesignRetrospective multicenter study.SettingTertiary referral center and private otology clinic.PatientsPatients who underwent transcanal endoscopic surgery between January 2015 and September 2020.Intervention(s)Transcanal endocope-assisted resection of middle ear paragangliomas.Main Outcome Measure(s)Demographic data.ResultsTwenty-three patients (2 men, 21 women) with a mean (standard deviation [SD]) age of 50.5 (11.8) years and stage 1 or 2 disease were included in the study. The mean follow-up time was 2.7 years (range, 1-5 yr). Preoperatively, the mean (SD) air-conduction threshold was 33.8 (17.9) dB, and the mean (SD) air-bone gap was 13.1 (13.9) dB. Postoperatively, the mean (SD) air-conduction threshold was 25.7 (10.2) dB, the mean (SD) air-bone gap was 6.3 (6.1) dB. The mean (SD) hospital stay was 27.7 (9.9) hours. No tumor regrowth was detected on magnetic resonance imaging during postoperative follow-up.ConclusionsEndoscopic transcanal tumor resection is effective and feasible in the treatment of stage 1 and 2 tumors and is associated with short operative time, low risk of perioperative and postoperative complications, and rapid discharge.
ACM Collective Intelligence Conference (CI) -- OCT 20-21, 2022 -- ELECTR NETWORK
Keywords: Endoscopic ear surgery; Glomus tumor; Middle ear paraganglioma; Transcanal